2019
DOI: 10.1016/j.wneu.2018.11.114
|View full text |Cite
|
Sign up to set email alerts
|

First United Kingdom Experience of Navigated Transcranial Magnetic Stimulation in Preoperative Mapping of Brain Tumors

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 53 publications
0
35
0
1
Order By: Relevance
“…Recently, some authors demonstrated the usefulness of rTMS language mapping especially in patients not eligible for awake surgery; 20,24,52,56 a few other studies analyzed the impact of this approach in patients operated on using awake surgery. 22,27,62,69,71 Conclusions from all these studies were in accord that nTMS-based language mapping enables a reliable identification of the language network, and allows for a tailored surgical strategy that may result in a good functional and even oncological outcome. Nevertheless, literature evidence currently consists of observational studies only, and no randomized clinical trials have been either organized or published so far.…”
Section: Neurosurgical Use-current Evidencementioning
confidence: 66%
“…Recently, some authors demonstrated the usefulness of rTMS language mapping especially in patients not eligible for awake surgery; 20,24,52,56 a few other studies analyzed the impact of this approach in patients operated on using awake surgery. 22,27,62,69,71 Conclusions from all these studies were in accord that nTMS-based language mapping enables a reliable identification of the language network, and allows for a tailored surgical strategy that may result in a good functional and even oncological outcome. Nevertheless, literature evidence currently consists of observational studies only, and no randomized clinical trials have been either organized or published so far.…”
Section: Neurosurgical Use-current Evidencementioning
confidence: 66%
“…Through nTMS it is possible to accurately map eloquent and motor areas using magnetic stimulation. nTMS can significantly reduce surgical time and guarantee a better functional outcome if coupled intraoperatively with DES ( 41 ). fMRI, nTMS, and DES guarantee a continuous control of motor, sensory or language domains on awake patients, thus ensuring a more radical excision according to functional boundaries ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative mapping of the primary motor cortex was performed with nTMS, according to the protocol previously described by our group using Nexstim, v.4.3.1 (Nexstim, Helsinki, Finland). 2 Briefly, a single-pulse sequence was delivered using a figure-of-eight coil, and the motor mapping was performed at 105% of the determined resting motor threshold (lowest stimulation intensity capable of eliciting a motor evoked potential [MEP]).…”
Section: Methodsmentioning
confidence: 99%
“…In the last decade, nTMS has emerged for preoperative brain mapping in patients with tumors in motor and language-eloquent areas. 2,[11][12][13] The nTMS uses a figure-ofeight stimulation coil, matched with neuronavigation, to deliver biphasic magnetic stimulation to the cortex. Singlepulse nTMS, applied to the primary motor cortex, generates muscle output that is recorded via a continuously running electromyogram.…”
Section: Introductionmentioning
confidence: 99%